Mathematical knowledge in the Grand Duchy of Lithuania - Rudenka, Alena (Poznańskie Studia Slawistyczne, 2024)
The article is devoted to mathematical knowledge in the Grand Duchy of Lithuania. This fragment of the linguistic worldview of the inhabitants of the GDL is modelled on the basis of the other authors’ works and the study of the relevant Ruthenian vocabulary. It is argued that education was widespread due to the multi-confessionalism of the GDL. Ruthenian names for counting and measurement, selected from the dictionaries of the Old Belarusian and Old Ukrainian languages, are considered in the article as a lexical-semantic field with several groups: numbers, arithmetic concepts and operations; units of measurements, weight, currency; types of profits, benefits, taxes. It is concluded that, according to the Ruthenian language, mathematical knowledge in the GDL is represented by: 1) arithmetic concepts and operations; 2) applied knowledge related to agriculture, handicrafts, trade, and social organisation of society; 3) abstract mathematical concepts, denoted by Latin borrowings.